Про узагальнену конфлюентну гіпергеометричну функцію Ψτ,β(a; c; z) - Вірченко, Н.О.; Лисецька, О.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The (τ, β) - generalized conﬂuent hypergeometric function Ψτ,β(a; c; z) is introduced. Some
properties of this function and its applications are given.